A look at the ground: time lapse camera trapping to determine the composition and abundance of small sized wildlife communities - García-López, V.; Vicente, J.; Carro, F.; Acevedo, P.; Ertürk, A. (Cold Spring Harbor Laboratory, 2025)
Abstract Micromammals are critical species in the context of ecosystem functioning, assuming a significant role as prey species and environmental engineers. Nevertheless, they present a challenge when developing monitoring programs. As a proof of concept, a time-lapse based camera-trapping non-invasive protocol was tested with the application of the Space to Event Model (STE) was determined. The objective of this study was to estimate the density of micromammals in Doñana National Park (DNP, Southwest Spain) by comparing estimates against independent ones obtained from capture-mark-recapture (CRM) methodology with a standardized protocol using Sherman traps. The micromammal species richness in the area exhibited a strong correlation with the capture methodology employed. Regarding the estimation of abundance, the densities of micromammals determined by STE were found to be within the range of the estimations of minimum population size determined by CRM. The STE, which was found to be promising, also allowed the determination of the abundance of other small-sized terrestrial wildlife, such as reptiles. Our findings indicate its potential for camera trap multi-species monitoring. In terms of practicability, field and data processing efforts for STE are both viable and will continue to improve as new automatic identification tools are incorporated. It is imperative that the STE protocols are examined in a series of study areas exhibiting varying micromammal densities and species compositions, in addition to other small-sized terrestrial wildlife.